Differences in Method-Specific Vancomycin MICs and Induced Daptomycin Resistance in an Infective Endocarditis Patient - David Benjamin Lash; Jeremiah Joson; Arash Heidari (Case Reports in Infectious Diseases)
Methicillin-resistant Staphylococcus aureus (MRSA) is a common nosocomial infection that has a high burden of morbidity and mortality. Vancomycin is the often-used antibiotic of choice when MRSA is suspected as a causative infectious agent. Recent studies have called into question the reliability of vancomycin as empiric therapy, especially in instances of bacteremia. The isolate’s minimum inhibitory concentration (MIC), the source of infection, modality of susceptibility testing, and antibiotic resistance are all issues that should be taken into consideration when formulating a care plan for a patient. We present a case that illustrates some of these issues clinicians are facing.